A new case with Hermansky-Pudlak syndrome type 9, a rare cause of syndromic albinism with severe defect of platelets dense bodies. (3rd April 2021) - Michaud, Vincent; Fiore, Mathieu; Coste, Valentine; Huguenin, Yoann; Bordet, Jean-Claude; Plaisant, Claudio; Lasseaux, Eulalie; Morice-Picard, Fanny; Arveiler, Benoit
Abstract: Hermansky-Pudlak syndrome (HPS) is a rare form of syndromic oculocutaneous albinism caused by disorders in lysosome‐related organelles. Ten genes are associated with different forms of HPS. HPS type 9 (HPS-9) is caused by biallelic variants of BLOC1S6 . To date, only three patients with HPS-9 have been reported. We described one patient presenting with ocular features of albinism. Genetic analysis revealed two compound heterozygous variants in the BLOC1S6 gene. Extended hematological studies confirmed the platelet storage pool disease with absence of dense granules and abnormal platelet aggregation. By reviewing the previous published cases we confirm the phenotype of HPS-9 patients. This patient is the only one described with dextrocardia and abnormal psychomotor development.